Program Edukasi Untuk Pelaku UMKM Dalam Pencatatan dan Penyusunan Laporan Keuangan Secara Sederhana - Nikmatul Lailiyah; Kafidin Muzakki (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This community service program is carried out with the aim of providing education for MSME players regarding the importance of recording and preparing financial reports in a simple way, in this case, for CV MSMEs. Mysneaker Retail Indo. This program is a discussion-based socialization program which aims to make the material presented easy to understand and understand and can help answer the problems faced by CV. Mysneaker Retail Indo in recording transactions and financial reports for their business. The results of this program show that CV. Mysneaker Retail Indo is interested in overhauling their financial report recording in the manner proposed by the author. According to them, by recording the financial reports submitted by the author, they can be used to read the business situation easily. This shows that this program is useful for increasing insight for MSME players in recording and preparing financial reports for their business.